Transnational connections and the Arab Gulf - Al-Rasheed, Madawi (Transnationalism. Routledge research in transnationalism, 2005)
This book challenges the definitions of globalisation and transnationalism as a one way process generated mainly by the Western World and the view that the latter is a twentieth century phenomenon.